Simulation study of a heterocatalytic reactor - Varga, Tamás; Abonyi, János; Szeifert, Ferenc (Acta Agraria Kaposváriensis, 2006)
The reactor runaway phenomenon is a serious problem in the chemical industry. In this work we focus on one of these runaway problems. Reactor runaway means a sudden and considerable change in the process variables. Runaway has two main important aspects. In one hand runaway forecast has a safety aspect, since it is important for avoiding the damage of reactor’s constructional material or reactor explosion; on the other hand it has a technology aspect, since the forecast of the runaway can be used for avoiding the development of hot spots in catalytic bed. Most of different runaway criteria found in literature are basically based on two approaches, there are data- and model-based criteria. The problem with the data-based methods is found in measurement conditions. The model-based criteria require parameterstability analysis, that means to apply a model-based criteria is necessary to have an exact model and correct model parameters. This thesis applies the Ljapunov’s indirect method to study the stability of an industrial reactor, and presents the how the steady-state simulator of the reactor can be used for the forecasting of the runaway in a catalytic tube-reactor. Based on the results extracted from this analysis a decision tree was inducted in order to be applied as part of an operator support system. This device is suitable for forecasting the reactor runaway based on the measured feed parameters.